Allelopathic effect of Carthamus tinctorius on weeds and crops - Motamedi,Marzieh (2020)
Abstract Background: Allelopathic plants like safflower (Carthamus tinctorius) can be considered as natural herbicides for weeds management in field. But there is not enough research on safflower genotypes allelopathy potential. Objective: So in this study, allelopathic effect of the four safflower genotypes on weeds (Amaranthussp., Hordeum spontaneum), crops (Sesamum indicum, Triticum aestivum) and on autotoxicity of Carthamus tinctorius was evaluated in bioassay using sandwich method. The results can be used in the management of weeds in safflower fields and also in the rotation with other crops. Methods: Two genotypes with high allelopathic potential and two genotypes with low allelopathic potential were selected from forty genotypes of safflower. Growth traits including radicle length, hypocotyl length, shoot length, fresh biomass weight and germination percentages were measured. Results: Results showed that Amaranthussp. and C. tinctorius displayed the most and least susceptibility to safflower residues, respectively. Khorasan (Khorasan330) and Egypt (PI657800) had the greatest with Kerman (CTNIR9) and Australia (PI 262424) had the least inhibitory effects on target plants. PI 262424 stimulated hypocotyl growth by 51%, 18% and 7% in H. spontaneum, T. aestivum and C. tinctorius, respectively. CTNIR9 enhanced this trait by 16% in T. aestivum and 10% in C. tinctorius. In large-seeded species (H. spontaneum, T. aestivum and C. tinctorius, Kerman (CTNIR9) and Australia (PI 262424) stimulated seedling growth. Conclusion: It can be concluded that effectiveness of allelopathic residues of safflower on target plants depended on the seed size of target plant with smaller seed size (Amaranthussp.) were more susceptible to allelopathic residues than those with larger ones. In addition radicle length was affected more than other growth traits by safflower residues.